Personality changes in couples: Partnership longevity and personality congruence in couples - Beatrice Rammstedt; Frank M. Spinath; David Richter; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Evidence of assortative mating according to personality was reported in a previous SOEP-based study (Rammstedt & Schupp, 2008). Based on population representative data of almost 7,000 couples, high levels of congruence between spouses were found, which increased with marriage duration. Almost 5,000 of these couples were tracked over a five-year period with personality assessed at the beginning and end of this time, which allowed us to investigate the relationship between personality congruence and marriage duration longitudinally. Using this data, we investigated (a) whether personality congruence is predictive for partnership longevity and whether congruence therefore differs between subsequently stable and instable couples, (b) if stable couples become more congruent, and (c) if separated couples become less congruent with regard to their personality over time. The results provide initial evidence of personality congruence as a predictor for partnership longevity: the more congruent couples are in the personality domain of Openness, the more stable their partnership. In addition, we found no indications of an increase in personality congruence over time within the stable couples; within the separated couples, however, a strong decrease in congruence was detectable.
Keywords: 330; assortative mating; Big Five; personality; congruence; personality change; partnership